Proceedings of the 7th Indian Young Geotechnical Engineers Conference 7IYGEC - 2019 - Dey, Ashim Kanti; Mandal, Jagat Jyoti; Manna, Bappaditya; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book comprises the select peer-reviewed papers presented at the 7th Indian Young Geotechnical Engineers Conference (7IYGEC 2019) held at the National Institute of Technology, Silchar. It covers recent research developments in geotechnical engineering particularly in the fields of shallow and deep foundations, rock mechanics, ground improvement techniques, geotechnical earthquake engineering, and characterization of soil. The book also discusses several computational techniques to model behavior of soil which can be useful for future research. A special emphasis is given on geo-environmental engineering for making the world cleaner and safer to live. Given the contents, the book will be beneficial for students, researchers, and professionals working in geotechnical engineering and allied areas.
Parametric Influence on the Behavior of Skirted Foundation -- Dynamic Analysis of Cantilever Sheet Pile Walls in Liquefiable Soil Using FLAC2D -- Bearing Capacity of Strip Footing Over Rectangular Tunnel in Soft Clay -- Combined Effect of Vertical and Horizontal Loads on the Behavior of Pile Foundations in Layered Soils -- Behavior of Laterally Loaded Piles using Finite Difference Method -- Bearing Capacity of Strip Footing Placed on Reinforced Cohesionless Soil Slope using Conic Programming -- Optimizing the Bearing Capacity of Pile Foundation in Clay -- Numerical Analysis of Soft Soil Reinforced with Geogrid Encased Stone Column -- Behaviour of Multi-Layer-Geocell Reinforced Soil Embankment -- Parametric Effect on Granular Columns: A Brief Review.
Keywords: Engineering geology; Geotechnical engineering; Surveying; Geographic information systems; Geoengineering; Geotechnical Engineering and Applied Earth Sciences; Surveying; Geographical Information System; Geotechnical engineering -- India -- Congresses